Test-retest reliability and clinical feasibility of a motion-controlled game to enhance the literacy and numeracy skills of young individuals with intellectual disability - Guarnieri R. (2019)
© Mary Ann Liebert, Inc., publishers 2019.Games using motion capture from web cameras have become increasingly popular. However, there are no games specifically designed to teach literacy to individuals with intellectual disabilities (ID). The aim of this study was to investigate the feasibility of introducing young individuals with ID to a new augmented reality game, the MoviLetrando, and establish its test-retest reliability to determine its usefulness in teaching the alphabet and motor control skills. The performance of a sample of 88 ID participants (52 males, 36 females, mean ± standard deviation age, 11.2 ± 2.6 years) was measured on two different testing sessions. Five dependent variables (total points, number of correct vowels/numbers, number of mistakes, number of omissions, and average time to reach symbols) were used for data analysis. The intraclass correlation coefficient (ICC), standard error of measurement (SEM), Cronbach's alpha, and Bland-Altman plots were used to estimate the test-retest reliability and measurement precision. Feasibility was assessed by examining recruitment, adherence, and acceptability in both phases of the game. The dependent variables identified in the MoviLetrando demonstrated an ICC of 0.44 to 0.82, suggesting acceptable/good test-retest reliability, respectively. The internal consistency was satisfactory. The small SEM, as well as the narrow width of the 95 percent limits of agreement in the Bland-Altman plots, implied that measurements of these dependent variables were precise and accurate on both the occasions. Excellent test-retest reliability for performance measurement was demonstrated in the ID participants, indicating that the MoviLetrando could be used as an outcome measure for this population.